Inequalities in unmet need for health care services and medications in Brazil: a decomposition analysisResearch in context - Maíra Coube; Zlatko Nikoloski; Matías Mrejen; Elias Mossialos (The Lancet Regional Health. Americas, 2023)
Summary: Background: Unmet need is a metric used to assess the performance of health care systems throughout the world. One of the primary objectives of the Brazilian health care system is to identify ways to improve the health outcomes of all citizens. To accomplish this challenging goal, the health care system in Brazil will need to identify and eliminate barriers and provide timely and adequate access to health care services to all. Methods: This study assessed the performance of the Brazilian health care system by focusing on the unmet need for health care services and medications. We evaluated the Brazilian National Health Survey data collected in 2013 and 2019 to determine the magnitude of socioeconomic-related inequalities associated with unmet health care needs. Primary contributing factors were identified via decomposition analysis of the calculated concentration indices (CInds). Findings: Despite the availability of universal health care, 3.8% and 7.5% of the population in Brazil reported unmet needs for health care services and medications, respectively in the 2019 survey. Although the overall unmet need for medications remained unchanged between 2013 and 2019, CInd analysis revealed significant pro-poor inequalities with respect to unmet needs for both health care services and medications. The overall magnitude of these inequalities was higher in the poorer regions of the country. The use of private health insurance as well as individual health and socioeconomic status contributed significantly to the inequalities associated with unmet needs for health care services and medication throughout Brazil. Interpretations: Policy interventions should focus on improving access to health care services, extending coverage to include pharmaceuticals, and targeting both financial and non-financial barriers to obtaining care, particularly those experienced by the poor and vulnerable populations in Brazil. Funding: None.